Pengaruh Labelisasi Halal, Brand Image, dan Religiusitas terhadap Keputusan Pembelian Mi Samyang pada Generasi Z - Murdayana, Murdayana; Rokhman, Nur (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2025)
This research aims to determine the influence of halal labeling, brand image and religiosity on the decision to purchase Samyang noodles in generation Z. The type of research used in this research is quantitative which is tested with multiple linear regression analysis using the SPSS for windows software program. The population in this research is all consumers who were born in the period 1997 to 2008, are Muslim, and have purchased Samyang noodles. The sampling technique uses non-probability sampling with a purposive sampling method. The total sample was 197 respondents. The data collection method uses a questionnaire announced via Google Form. The results of this research show that halal labeling and brand image have no influence on purchasing decisions, while the religiosity variable has an influence on purchasing decisions.